A young Female of Cowden Syndrome Presenting with Lhermitte- Duclos Disease: A Case Study - Noman, Abdullah Al; Mokbul, Mobin Ibne; Rana, Md Sumon; Hasan, Md Motasimul; Islam, Md Shafiqul; Hossain, A B M Manwar; Asaduzzaman, S M (Bangladesh Journal of Neurosurgery, 2023)
Cowden Syndrome (CS) is a rare autosomal dominant inherited genetic disorder due to germline mutations in the phosphatase and tensing homologue (PTEN) tumor suppressor gene in chromosome 10 characterized by multiple hamartomata’s lesions of ectodermal, mesodermal and endodermal origin. Lhermitte-Duclos Disease (LDD), or dysplastic gangliocytoma, which is a benign hamartomata’s condition involving the cerebellum with less than 300 cases reported in the literature. Previous studies suggest an association between CS and LDD. We present here a case of a 28-year female patient presented at the emergency department of our hospital with severe headache associated with vertigo, vomiting & cerebellar ataxia. Papilledema was noted on fundoscopy. Non-attenuating hypodense mass lesion in posterior fossa was found in CT scan. MRI scan T1WI film revealed mixed intensity posterior fossa lesion and T2WI film revealed inhomogeneous hyperintense lesion with almost preserved cerebellar cortical striations. USG revealed numerous polyps in the gallbladder with cholelithiasis. Her facial skin has extensive trichilemmoma. Her symptoms improved after excision of posterior fossa lesion through suboccipital craniectomy and histopathology revealed dysplastic cerebellar gangliocytoma i.e., Lhermitte-Duclos disease. Using the Cleveland Clinic Adult Clinical Scoring for PTEN Testing, the patient had an 82-98% chance for a PTEN gene mutation. Finally, she along with her family was adequately counseled and was advised for regular screening and monitoring. Bang. J Neurosurgery 2022; 12(1): 41-46